MEMILIH SEKOLAH DASAR UNTUK ANAK MENGGUNAKAN FUZZY LOGIC METODE MAMDANI: CHOOSING ELEMENTARY SCHOOL FOR CHILDREN USING FUZZY LOGIC MAMDANI METHOD - Nia Ekawati; Elsari Fatkhur Jannati (Asosiasi Ide Bahasa Kepri, 2022)
Education Batam City has an education that follows the development of the current era. Because the city of Batam itself is very close to neighboring countries, namely Singapore and Malaysia. As reported from the online electronic media Kompas newspaper on January 17, 2017, as a parent, of course you also don't want to look for a school for your baby. The reason is, choosing the right school, especially kindergarten (TK) and elementary school (SD), is a